Analisis dampak Artificial Intelligence (AI) terhadap Sektor Tenaga Kerja di Indonesia - Yoel Edward Hasugian (Majelis: Jurnal Hukum Indonesia, 2026)
The rapid advancement of Artificial Intelligence (AI) has significantly disrupted the global labor sector, including in Indonesia. The urgency of this study lies in the growing inequality in access to digital skills and the lack of legal protection for workers in the digital era. This research aims to analyze the impact of AI on employment in Indonesia and to assess the adequacy of labor regulations in addressing digital transformation. This study employs a normative legal method with a juridical-empirical approach, utilizing literature review, secondary data, and qualitative analysis of labor policies and relevant regulations. The findings reveal that while AI has the potential to create new types of employment, it also threatens conventional jobs, especially in labor-intensive sectors. Moreover, Indonesia's labor regulations have not yet adapted to new, flexible, and platform-based work models, resulting in legal uncertainty for informal and freelance workers. This study contributes to the discourse on the need for labor law reform that is inclusive and adaptive to technological developments. In conclusion, there is a pressing need for responsive labor regulation reform, increased digital literacy, and continuous reskilling systems to ensure that AI-driven transformation does not create new inequalities in the labor market. Future research is recommended to focus on formulating new legal protection models for digital workers in the AI era.